'That's Witchcraft': Community entrepreneuring as a process of navigating intra-community tensions through spiritual practices. Issue 2 (February 2022) - Cucchi, Carlo; Lubberink, Rob; Dentoni, Domenico; Gartner, William B.
This paper theorizes the spiritual processes of community entrepreneuring as navigating tensions that arise when community-based enterprises (CBEs) emerge within communities and generate socio-economic inequality. Grounded on an ethnographic study of a dairy CBE in rural Malawi, findings reveal that intra-community tensions revolve around the occurrence of 'bad events' – mysterious tragedies that, among their multiple meanings, are also framed as witchcraft. Community members prepare for, frame, cope and build collective sustenance from 'bad events' by intertwining witchcraft and mundane socio-material practices. Together, these practices reflect the mystery and the ambiguity that surround 'bad events' and prevent intra-community tensions from overtly erupting. Through witchcraft, intra-community tensions are channelled, amplified and tamed cyclically as this process first destabilizes community social order and then restabilizes it after partial compensation for socio-economic inequality. Generalizing beyond witchcraft, this spiritual view of community entrepreneuring enriches our understanding of entrepreneuring – meant as organization-creation process in an already organized world – in the context of communities. Furthermore, it sheds light on the dynamics of socio-economic inequality surrounding CBEs, and on how spirituality helps community members to cope with inequality and its effects.